Deep Phosphoproteomic Measurements Pinpointing Drug Induced Protective Mechanisms in Neuronal Cells - Yu, Chengli; Gao, Jing; Zhou, Yanting; Chen, Xiangling; Xiao, Ruoxuan; Zheng, Jing; Liu, Yansheng; Zhou, Hu (Frontiers in Physiology, 2016)
Alzheimer's disease (AD) is a progressive and irreversible neurological disorder that impairs the living quality of old population and even life spans. New compounds have shown potential inneuroprotective effects in AD, such as GFKP-19, a 2-pyrrolidone derivative which has been proved to enhance the memory of dysmnesia mouse. The molecular mechanisms remain to be established for these drug candidates. Large-scale phosphoproteomic approach has been evolved rapidly in the last several years, which holds the potential to provide a useful toolkit to understand cellular signaling underlying drug effects. To establish and test such a method, we accurately analyzed the deep quantitative phosphoproteome of the neuro-2a cells treated with and without GFKP-19 using triple SILAC labeling. A total of 14,761 Class I phosphosites were quantified between controls, damaged, and protected conditions using the high resolution mass spectrometry, with a decent inter-mass spectrometer reproducibility for even subtle regulatory events. Our data suggests that GFKP-19 can reverse Aβ25-35 induced phosphorylation change in neuro-2a cells, and might protect the neuron system in two ways: firstly, it may decrease oxidative damage and inflammation induced by NO via down regulating the phosphorylation of nitric oxide synthase NOS1 at S847; Secondly, it may decrease tau protein phosphorylation through down-regulating the phosphorylation level of MAPK14 at T180. All mass spectrometry data are available via ProteomeXchange with identifier PXD005312.